Penentuan Jenis Fluida Reservoar Di Lapangan M, Blok N, Sumatera Selatan - Nugroho Marsiyanto (Department of Petroleum Engineering, 2022)
Reservoir fluid type in oil or gas field must be determined very early in the life of reservoir because it is as critical factor in many of decisions made about producing strategy of the fluid from the reservoir. It also influence in the depletion reservoirs strategy. Reservoir fluid type can be confirmed only by observing a representative fluid sample in the laboratory testing. However, rules of thumb based on production data such as initial producing GOR, stock tank liquid gravity, and stock tank liquid color usually will indicate reservoir fluid type of those reservoirs. M field was discovered in December 1989 with the drilling of M-1 well. Subsequently, in July 1991, the M-2 well was drilled. In November 1997, an appraisal well, M-3, was drilled. Based on total production testing at M field indicated that the potential deliverability is 30 MMSCFD and M field have being produced since March 2002 up to date from those three wells. Objective of this paper is to determine fluid type in this M field. Based on the laboratory testing data from those 3 wells, the heptane plus concentration of M1 well is 0.47 % mole, the heptane plus concentration of M2 well is 0.67 % mole, and the heptane plus concentration of M3-well is 0.64 % mole. The Initial Gas Oil Ratio of M field refer to well testing is ranging from from 75,000 scf/STB to 554,545 scf/STB which is high GOR producing. Based on those 2 methods to determine reservoir fluid types, the laboratory testing and rules of thumb on intial production data, the fluid type of M field is categorized as A Dry Gas. This fluid determination is giving the advantages of strategic field drainage optimally and economically to the field.